MODEL PEMBELAJARAN SAINS MELALUI STIMULASI KECERDASAN NATURALIS - Farida Agus Setiawati (Jurnal Kependidikan, 2006)
Abstract This research aims to make the learning model that able to develop the natural intelligence suitable for the learning process of the first class of the elementary school. This research is the developing research based on the Borg and Gall’s model (1983). The product developed in this research is the science learning model. The experiment did in the SD Sultan Agung, Yogyakarta, involving 1 teacher and 24 students. Because of the lack of time and finance in research, the experiment was done only one school. The data are collected by observation documentation and interview. This data are analyzed descriptively and qualitatively. The result of this research showed that the teacher can stimulate the natural intelligence through the science learning model developed by the researcher. This model can also stimulate the student’s natural intelligence. The field experiments showed that the science learning developed to be implemented out of the class made the students more actives, more spirit, and cheerful than other activities done in  the class. The science learning done with giving more assignment made the students more actives than speech and interview method. Keywords: science learning model, stimulate natural intelligence.